Selective Attention and Consciousness: Investigating Their Relation Through Computational Modelling - Neokleous, Kleanthis C.; Avraamides, Marios N.; Schizas, Christos N.; Neocleous, Costas (My University, 2011)
The present study aimed at investigating the possible connection between conscious awareness and attention through the implementation of a neurocomputational model of visual selective attention. The development of the model was based on recent neurophysiological findings that document the synchronization of neural activity in cortical areas of the brain and the presence of competitive interactions among stimuli at the early stages of visual processing. The model was used to simulate the findings of a behavioural experiment conducted by Naccache et al. in Psychol Sci 13:416–424 (2002), which have sparked a debate on the possible links between attention and consciousness. The model reproduced closely the pattern of the behavioural data while incorporating mechanisms that take into account the neural activity representing the early visual processing of stimuli and the effects of top–down attention. Thus, by adopting a computational approach, we present a possible explanation of the findings at the neural level of information processing. The implications of these findings for the relation between attentional processes and conscious awareness are discussed.
Keywords: Spiking neural networks; Visual selective attention; Consciousness